Biohydrogen Production from Methane-Derived Biomass of Methanotroph and Microalgae by Clostridium - Yuxuan Sang; Zhangzhang Xie; Liangyan Li; Oumei Wang; Shiling Zheng; Fanghua Liu (Fermentation, 2024)
Methane, a potent greenhouse gas, represents both a challenge and an opportunity in the quest for sustainable energy. This work investigates the biotechnology for converting methane into clean, renewable hydrogen. The co-culture of Chlorella sacchrarophila FACHB 4 and Methylomonas sp. HYX-M1 was demonstrated to completely convert 1 mmol of methane to biomass within 96 h. After acid digestion of such biomass, up to 45.05 μmol of glucose, 4.07 μmol of xylose, and 26.5 μmol of lactic acid were obtained. Both Clostridium pasteurianum DSM525 and Clostridium sp. BZ-1 can utilize those sugars to produce hydrogen without any additional organic carbon sources. The higher light intensity in methane oxidation co-culture systems resulted in higher hydrogen production, with the BZ-1 strain producing up to 14.00 μmol of hydrogen, 8.19 μmol of lactate, and 6.09 μmol of butyrate from the co-culture biomass obtained at 12,000 lux. The results demonstrate that the co-culture biomass of microalgae and methanotroph has the potential to serve as a feedstock for dark fermentative hydrogen production. Our study highlights the complexities inherent in achieving efficient and complete methane-to-hydrogen conversion, positioning this biological approach as a pivotal yet demanding area of research for combating climate change and propelling the global energy transition.